Una nueva especie de lagartija del género Liolaemus (Iguania: Liolaemidae) endémica de la Puna del sur de Perú - Arapa, Laura Andrea (2021)
The Andes of southern Peru contain a biodiversity with high degree of endemism due to its peculiar geography and bioclimate. In this work a new endemic species of the genus Liolaemusis described which would be restricted to an altitude between 3870?4100 m s.n.m., in the Salado river basin of the district and province of Espinar, department of Cusco. This species is characterized by the unique combination of morphological characters and the color pattern that distinguish it from the rest of the species of the genus Liolaemus, mainly within of L. ortiziclade of the L. montanus group, where the new species is located according to our phylogenetic hypothesis based on morphological evidence presented in this study